A STUDY OF 100 CASES OF BILATERAL TOTAL KNEE REPLACEMENTS WITH ASYMMETRY OF COMPONENT SIZE - Bajwa, Mubashar Ahmed; Barki, Asad Ullah; Niazi, Auon Shabbir Khan; Khan, Abdul Qadir; Waqar, Sherish; Bajwa, G.R. (Pakistan Armed Forces Medical Journal, 2020)
Objective: Many studies have described the normal variations in the anatomy of the knee, however very few studies have reported the asymmetry of component size in bilateral total knee arthroplasties. Our study is the first one to find out the incidence of asymmetry of component size in bilateral total knee arthroplasties in Pakistan.Study Design:Place and Duration of Study: Rai Medical College, Sargodha, from Oct 2016 to Oct 2018.Methodology: We conducted a prospective analysis of 100 patients presenting to the orthopedic department of Doctors Trust Teaching Hospital affiliated with Rai Medical College, Sargodha between October 2016 and October 2018. Out of these 89 patients were operated in a single staged procedure whereas 11 were operated in a two staged (second knee at a 2-3 day interval) procedure. Implants used were Nexgen (Zimmer Biomet, Warsaw, IN, USA), Genesis II (Smith and Nephew, Memphis, TN, USA) and PFC-Sigma (DePuy, Warsaw, IN, USA).Data was analyzed using SPSS v.25.Results: Out of 100 patients 20% were found to have component size asymmetry with 12% in the femoral component only, 2% only in tibial component only, 3% in patellar component only, 2% having asymmetry in both femoral and tibial components and 1% having asymmetry in both femoral and patellar components. There was a similar incidence of component size asymmetry in all three different types of implants. Incidence of component size asymmetry in male and female patients was found to be 15.8% and 21% respectively.Conclusion: Since, 20% of the cases showed asymmetry of component size, we recommend that both knees should be measured for implant size individually rather than using the measurement of a single knee for both knees before a bilateral total knee arthroplasty.